Metabolome combined with transcriptome profiling reveals the dynamic changes in flavonoids in red and green leaves of Populus × euramericana ‘Zhonghuahongye’ - Yang, Yun; Chen, Mengjiao; Zhang, Wan; Zhu, Haiyang; Li, Hui; Niu, Xinjiang; Zhou, Zongshun; Hou, Xiaoya; Zhu, Jingle (Frontiers in Plant Science, 2023)
Flavonoids are secondary metabolites that have economic value and are essential for health. Poplar is a model perennial woody tree that is often used to study the regulatory mechanisms of flavonoid synthesis. We used a poplar bud mutant, the red leaf poplar variety 2025 (Populus × euramericana ‘Zhonghuahongye’), and green leaves as study materials and selected three stages of leaf color changes for evaluation. Phenotypic and biochemical analyses showed that the total flavonoid, polyphenol, and anthocyanin contents of red leaves were higher than those of green leaves in the first stage, and the young and tender leaves of the red leaf variety had higher antioxidant activity. The analyses of widely targeted metabolites identified a total of 273 flavonoid metabolites (114 flavones, 41 flavonols, 34 flavonoids, 25 flavanones, 21 anthocyanins, 18 polyphenols, 15 isoflavones, and 5 proanthocyanidins). The greatest difference among the metabolites was found in the first stage. Most flavonoids accumulated in red leaves, and eight anthocyanin compounds contributed to red leaf coloration. A comprehensive metabolomic analysis based on RNA-seq showed that most genes in the flavonoid and anthocyanin biosynthetic pathways were differentially expressed in the two types of leaves. The flavonoid synthesis genes CHS (chalcone synthase gene), FLS (flavonol synthase gene), and ANS (anthocyanidin synthase gene) and proanthocyanidin synthesis gene LAR (leucoanthocyanidin reductase gene) might play key roles in the differences in flavonoid metabolism. A correlation analysis of core metabolites and genes revealed several candidate regulators of flavonoid and anthocyanin biosynthesis, including five MYB (MYB domain), three bHLH (basic helix-loop-helix), and HY5 (elongated hypocotyl 5) transcription factors. This study provides a reference for the identification and utilization of flavonoid bioactive components in red leaf poplar and improves the understanding of the differences in metabolism and gene expression between red and green leaves at different developmental stages.